Compare Linear Progamming With Other Methods to Finding Optimal Solution for Transportation Problem - البدري فاتن فاروق; كواز حسين عدنان (Journal of Economics and Administrative Sciences, 2017)
The researcher studied transportation problem because it’s great importance in the country’s economy. This paper which ware studied several ways to find a solution closely to the optimization, has applied these methods to the practical reality by taking one oil derivatives which is benzene product, where the first purpose of this study is, how we can reduce the total costs of transportation for product of petrol from warehouses in the province of Baghdad, to some stations in the Karsh district and Rusafa in the same province. Secondly, how can we address the Domandes of each station by required quantity which is depending on absorptive capacity of the warehouses (quantities supply), And through results reached by the researcher find the best method came after linear programming was the exponential method because it gave a solution closely to the optimization as were the result linear programming (4,357,575), either the of result exponential method was (4,365,061) followed by method Ones Method amounting the total cost (4,371,841 ) and after the result approach (A.S.M) was the total cost (4,372,585) and there were other methods reported in the research gave a high cost compared with the methods mentioned above .